Phuket Street Food: STREET FOODS Model Providing a Creative Charm for Phuket’s Gastronomy Tourism - Chaiyasain, Chainun (WMS Journal of Management, 2020)
Street food business is considered to be a major part of the local economy. This important mechanism for expanding microeconomic stability can help to create an economic value to extend from the region to the country. In 2017, the street food market was worth 276,000 million baht and is expected to increase to 340,000 million baht in 2021. This provides for and increased growth average rate of 5.3 percent per year. There are approximately 103,000 street food restaurant operators or 69% of the restaurant service business in the region. Therefore, Phuket should develop and organize a street food business plan identifying its unique attraction for tourists. The street food business operators should comprehend and implement this model for the operation and management plan outlined in the “STREET FOODS Model” consisting of Sanitation and Safety, Taste, Research and Innovation, Exceed Service, Environmentally Friendly, Thai-ness, Food Identity, Online Marketing, Organize, Do it, and Supporting. Additionally, various government departments should provide a systematic support system accompanied by supervision in order to apply street food standards. Providing more attraction for tourist by upgrading the standard of service and creating a unique charm, for the street food businesses of Phuket while developing a city of gastronomy thus attracting world class tourists.